Sectoral Structures and Regional Economic Development in European Union - Magdalena CYREK; Piotr CYREK (Communications of International Proceedings, 2020)
The study deals with problems of sectoral structures of employment perceived as a determinant of economic results in terms of GDP per capita. The analysis is conducted for NUTS2 regions in European Union. The aim of the research is to identify clusters of regions basing on structural features of employment. To fulfill the task a Ward method is used. The paper verifies if the clusters with different sectoral labor distribution are simultaneously diversified concerning productive results of economic activity. Moreover, it is tested if the specified groups of regions are differentiated in terms of some selected indicators of human resources accessibility and labor market condition. Concerning the purpose, an analysis of variance is conducted. The results allow to conclude about positive relation between structural maturity and economic development for the EU regions. It suggests that some of regional economies may experience a middle-income trap, basing on traditional sectors and less intensive knowledge usage that limits possibilities for accelerated economic growth and improvement of quality of life. It is also found that more advanced economies in terms of sectoral structures are characterized by better human resources endowment, while sectoral labor distribution does not differentiate actual condition of a labor market. The research confirms a long-term character of the relations between sectoral structures and labor, that could be strengthen by economic policy supporting investments in human resources.
Keywords: sectoral structures; economic development; regions; European Union.